Recurrent Lower Abdominal Pain in Older Children and Adolescents: Revised Clinical Approach - Harohalli Shashidhar; Hatim A. Omar (The Scientific World Journal)
Pelvic and lower abdominal pain constitutes more than 30% of the referrals to our adolescent medicine and gastroenterology clinics. These cases are responsible for numerous school absences and significant cost to the healthcare system. This article will review the most common causes of lower abdominal and pelvic pain in adolescents, diagnostic and management issues, as well as prevention.